The effect of functional remission and cognitive insight on criminal behavior in patients with schizophrenia - Polat, Hatice; Ugur, Kerim; Aslanoglu, Eren; Yildiz, Sevler; Yagin, Fatma Hilal (W B Saunders Co-Elsevier Inc, 2023)
Objective: This study was planned to determine the relationship of functional remission with a criminal history and determine its effect on criminal behavior in patients with schizophrenia.Methods: This cross-sectional study was conducted with 132 patients with schizophrenia (66 with and 66 without a criminal history). Data were collected between November 2020 and April 2021 using a personal information form, the Functional Remission of General Schizophrenia (FROGS), the Taylor Crime Violence Rating Scale, the Beck Cognitive Insight Scale, and the Positive and Negative Syndrome Scale (PANSS) was used to collect data.Results: In terms of all scale variables, there were significant differences between the groups with and without a criminal history (p < 0.05). These differences were mostly clearly observed in the FROGS-social functionality (effect size: 16.79), PANSS-positive (effect size: 2.62) and FROGS-health and treatment (effect size: 2) subscales. Conclusions: In this study, it was determined that as the symptoms of the illness increased in schizophrenia, the patients' functional remission and insight decreased, and their tendency to commit crimes increased. Psychiatric nurses can plan therapeutic interventions to increase the functionality and insight levels of patients with schizophrenia.
Keywords: Functional remission; Forensic psychiatry; Schizophrenia